2014
DOI: 10.1007/s40477-014-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in obstructive lung diseases: the effect of airway obstruction on diaphragm kinetics. A short pictorial essay

Abstract: The ultrasound study of the chest is showing a continuous development. This technique could be helpful in managing several chest diseases, but it is limited to the acoustic windows provided by intercostal spaces and by the inability to study healthy lung parenchyma and all intraparenchymal diseases such as chronic obstructive lung disease (COPD), because the interaction between ventilated lung and ultrasound generates only artifacts. Currently, there are few applications of ultrasound that are useful in COPD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Indeed, a linear correlation between lung volumes and amplitude of diaphragm motion has already been proved [9]; furthermore, Zanforlin et al [22] have recently shown that the M-mode ultrasound forced expiratory profile presents similarities with the spirometric flow-volume curve. Consequently, ultrasound-derived indexes (i.e., forced diaphragmatic excursion in the first second or maximal expiratory diaphragm excursion, and the ratio of the 2) have a linear correlation with FEV1, FVC, and the FEV1/FVC ratio, both in healthy and obstructed subjects [23]. In addition, we were not able to test many variables potentially affecting the predictivity of diaphragm motion models.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, a linear correlation between lung volumes and amplitude of diaphragm motion has already been proved [9]; furthermore, Zanforlin et al [22] have recently shown that the M-mode ultrasound forced expiratory profile presents similarities with the spirometric flow-volume curve. Consequently, ultrasound-derived indexes (i.e., forced diaphragmatic excursion in the first second or maximal expiratory diaphragm excursion, and the ratio of the 2) have a linear correlation with FEV1, FVC, and the FEV1/FVC ratio, both in healthy and obstructed subjects [23]. In addition, we were not able to test many variables potentially affecting the predictivity of diaphragm motion models.…”
Section: Discussionmentioning
confidence: 86%
“…This will also represent the ideal opportunity to explore a wide range of emergent ultrasound measures to assess the short-term effects of PR on the structure and motion of the diaphragm and peripheral muscles (biceps and quadriceps). Ultrasonographic assessment of the rectus femoris muscle (thickness and cross sectional area) has been found to be correlated with muscle strength [70], and some measures of diaphragmatic kinetics have been proposed as promising to study disease progression (e.g., MIO) [73, 74] and prognosis of PR outcomes (e.g. change in the diaphragmatic length of zone of apposition at functional residual capacity ΔLzapp%) [109].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the following secondary outcomes will be assessed: symptoms of dyspnoea (modified Medical Research Council Questionnaire [mMRC]) [51], fatigue (Checklist of individual strength [CIS-20]) [52] and Functional assessment of chronic illness therapy – fatigue [FACIT-F]) [53, 54], cough and sputum (Leicester cough questionnaire [LCQ] [55] and Cough and sputum assessment questionnaire [CASA-Q]) [56], impact of the disease (COPD Assessment Test [CAT]) [57, 58], emotional status (The Hospital Anxiety and Depression Scale [HADS]) [59, 60], Family Adaptation and Cohesion Scales [FACES-IV]) [61, 62], peripheral (biceps and quadriceps with the hand held dynamometer, 1 [1-RM] or 10 [10-RM] repetition-maximum) [63, 64] and inspiratory and expiratory muscle strength (respiratory pressure meter) [65], exercise capacity (six-minute walk test [6MWT] and one-minute sit to stand test [1-min STS]) [66, 67], balance (brief-balance evaluation systems test [Brief-BESTest]) [68] and physical activity (accelerometer) [14]. Peripheral muscle (rectus femoris and biceps brachialli) and diaphragm thickness, cross sectional area [69, 70] and echointensity [71], excursion and M-Mode Index of Obstruction (MIO) [7274], will be measured with ultrasound images – ImageJ and Matlab software. Global rating of change scale [75] for fatigue, cough, sputum, peripheral and respiratory muscle strength and balance will also be collected.…”
Section: Methodsmentioning
confidence: 99%
“…In analogy to the time/volume curve of spirometry, the calculated M-mode Index of Obstruction (MIO) from the ratio between forced diaphragmatic excursion in the first second and the maximal expiratory diaphragmatic excursion correlates linearly with airway obstruction [58]. In the general clinical setting, the detection of abnormalities in respiratory motion can contribute to the early detection of COPD as an ancillary finding in abdominal ultrasound [59].…”
Section: Obstructive Lung Diseasesmentioning
confidence: 99%